Electrochemical Characterization of Graphene and Mwcnt Screen-Printed Electrodes Modified with Aunps for Laccase Biosensor Development - Tasca-Gottardo, F; Tasca-Gottardo, F (Multidisciplinary Digital Publishing Institute (MDPI), 2015)
The aim of this work is to show how the integration of gold nanoparticles (AuNPs) into multi-wall-carbon-nanotubes (MWCNTs) based screen-printed electrodes and into graphene-based screen-printed electrodes (GPHs) could represent a potential way to further enhance the electrochemical properties of those electrodes based on nanoparticles. Laccase from Trametes versicolor (TvL) was immobilized over MWCNTs and GPH previously modified with AuNPs (of 5 and 10 nm). The characterization of the modified electrode surface has been carried out by cyclic voltammetry. The results showed that the use of AuNPs for modification of both graphene and MWCNTs screen-printed electrode surfaces would increase the electrochemical performances of the electrodes. MWCNTs showed better results than GPH in terms of higher electroactive area formation after modification with AuNPs. The two modified nanostructured electrodes were successively proven to efficiently immobilize the TvL; the electrochemical sensing properties of the GPH-and MWCNT-based AuNPs-TvL biosensors were investigated by choosing 2,2ʹ-Azino-bis(3-ethylbenzothiazoline-6-sulfonic-acid diammonium salt (ABTS), catechol and caffeic acid as laccase mediators; and the kinetic parameters of the laccase biosensor were carefully evaluated. © 2015 by the authors; licensee MDPI, Basel, Switzerland.